Vertically aligned two-dimensional halide perovskites for reliably operable artificial synapses. (January 2022) - Kim, Seung Ju; Lee, Tae Hyung; Yang, June-Mo; Yang, Jin Wook; Lee, Yoon Jung; Choi, Min-Ju; Lee, Sol A; Suh, Jun Min; Kwak, Kyung Ju; Baek, Ji Hyun; Im, In Hyuk; Lee, Da Eun; et al.
Graphical abstract: Abstract: Halide perovskites, fascinating memristive materials owing to mixed ionic-electronic conductivity, have been attracting great attention as artificial synapses recently. However, polycrystalline nature in thin film form and instability under ambient air hamper them to be implemented in demonstrating reliable neuromorphic devices. Here, we successfully fabricated vertically aligned 2D halide perovskite films (V-HPs) for active layers of artificial synapses, showing moisture stability for several months. Unlike random-oriented HPs, which exhibit negligible current hysteresis, the V-HPs possess multilevel analog memristive characteristics, programmable potentiation and depression with distinguished multi-states, long-short-term plasticity, paired-pulse facilitation, and even spike-timing-dependent plasticity. Furthermore, high classification accuracy is obtained with implementation in deep neural networks. These remarkable improvements are attributed to the vertically well-aligned lead iodide octahedra acting as the ion transport channel, confirmed by first-principles calculations. This study paves the way for understanding HPs nanophysics and demonstrating their potential utility in neuromorphic computing systems.